Keadilan Restoratif dan Korban Pelanggaran HAM (Sebuah Telaah Awal) - Yulia, Rena (Jurnal Hukum dan Peradilan, 2012)
Various violations on human right happening in Indonesia today have never been completely solved. Victims of human right violations (direct or indirect victims) find it difficult to access justice through the existing criminal law today. Difficulties in proving the violations committed by the actors make it harder for the justice to be in the victim’s side. For any reasons, the violations of human rights should be brought into the court. It is surely not easy to do so as the retributive justice applied so far has not been able to solve the existing problems and to give fairness to the victims. Restorative justice is therefore considered as a potential way out for a justice to take place for the crime actors, victims and society in general. In various types of criminal actions such as domestic violence, law –violatingchildren and traffic crime, the restorative justice has been successfully applied and it is now under evaluation in human right related cases. This is done in order to find out the effectiveness of this restorative justice in solving those cases. This writing aims to find out opportunities for the restorative justice implementation in solving human right violations in Indonesia. Keywords: Human Right violation victims, restorative justice, rehabilitation.